Linguistic and cognitive interpretation of art work of an author (on the example of Yuri Mushketyk’s works «Старий у задумі» і «Сльоза Офелії» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is devoted to the revealing of cognitive parameters of interpretation of Yuri Mushketyk’s creation. Masterful way, reproduced in Yuri Mushketyk’s creation, correlates with the path of life, which is the master's fate. Since finding of the artistic image  combines not only a search of  the means of expression, but also hard work, writer interprets the concept of beauty, perfection, harmony through author’s ability to feel their content on the level of inner world – the soul. In the works of «Старий у задумі» і «Сльоза Офелії» a stage of the creative process, which is in observing and experiencing the events on the example of autobiographical way, interprets the content of life perception solely on brightness, sincerity, depth, on the meaningfulness of the feeling that in the creative framing is embodied in artistic image (technique (skillfulness) in the using of artistic means – vigorousness of the inner world – creativity).Essence of the art further in Yuri Mushketyk’s stories uncovers on the basis of close relationship of sensory and rational rudiments. Contemplation of the art work promotes interaction that makes possible decoding of an artistic image according to the level of aesthetic threshold and experience. In the artistic interpretation of a work of art the figurativeness is related to the conceptual thinking on the basis of comparison, differentiation, grouping, correlation of created images pursuant to certain ideals, conceptions as  the author’s strictly, and those that have found  consistent coverage at the level of national / world culture. The terminal component of the life in the reproducible biographical line of a sculptor correlates with socio-cultural and spiritual levels.
Keywords: linguistic and cognitive interpretation; language categorization; sacral concept; art image; aesthetics of an artwork